Clinical and molecular characterization of Turkish patients with familial hypomagnesaemia: novel mutations in TRPM6 and CLDN16 genes - BEREKET, ABDULLAH; DEMİRCİOĞLU, SERAP; GÜRAN, TÜLAY (OXFORD UNIV PRESS, 2012)
Recent identification and characterization of novel renal Mg2+ transporters and ion channels have greatly increased our understanding of the normal physiology of renal magnesium handling. The present study deals with the clinical and molecular characterization of eight Turkish children (median age 10.6 years, range 3-16.2 years, five boys and three girls) with primary hypomagnesaemia from six families. All patients initially presented with tetany and convulsions. Laboratory evaluation yielded severely low serum magnesium levels and low serum calcium levels in all patients. While six patients exhibited inadequately low parathyroid hormone levels, the two remaining patients showed hyperparathyroidism, hypercalciuria and nephrocalcinosis. Genetic studies revealed familial hypomagnesaemia with secondary hypocalcaemia (HSH) due to a TRPM6 mutation in six patients and familial hypomagnesaemia with hypercalciuria and nephrocalcinosis (FHHNC) due to a CLDN16 mutation in one patient. Among recently identified magnesium-wasting disorders, HSH and FHHNC represent two major entities also in the Turkish population. Besides clinical course and laboratory diagnosis of hypomagnesaemia, the detection of renal calcium wasting and parathyroid function are crucial to differentiate between these most prevalent forms of hereditary magnesium deficiency. While TRPM6 mutations underlying HSH almost uniformly lead to a complete loss of function of the TRPM6 protein, the severity of FHHNC phenotype depends on the residual function of the mutated claudin-16 protein.
Keywords: claudin-16; CLDN16; familial hypomagnesaemia; TRPM6; SECONDARY HYPOCALCEMIA; MAGNESIUM HOMEOSTASIS; NEPHROCALCINOSIS; HYPERCALCIURIA; PARACELLIN-1; DISORDERS